FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Neessy Neessy; Augustpaosa Nariman (Jurnal Paradigma Akuntansi, 2026)
The purpose of this research is to determine factors in this study influence capital structure consisting of liquidity, profitability, aset structure and firm size in manufacturing companies in consumer non cyclicals sectors listed in Indonesia Stock Exchange in 2019-2021. Purposive Sampling was used in this study sampling, which resulted in 132 form 44 companies. Data processing uses Eviews version 12. The result showed that liquidity, profitability, asset structure and firmsize has negative substantial impact on capital structure.